IMPROVING THE COMPANY’S FINANCIAL METHODS - Bekbayeva Feruza Baxtiyerovna (Scholar Express Journals, 2024)
This article explores strategies for enhancing a company's financial methodologies to foster sustainable growth and resilience in dynamic business environments. It examines various approaches aimed at optimizing financial processes, including budgeting, forecasting, cost control, and capital allocation. By leveraging advanced technologies, embracing innovative practices, and prioritizing strategic decision-making, organizations can streamline their financial operations and adapt proactively to market fluctuations. Through case studies and empirical analysis, this study elucidates the significance of efficient financial management in driving competitiveness and achieving long-term financial objectives
Keywords: Financial management; Financial methodologies; Budgeting; Forecasting